2011
DOI: 10.3390/molecules161210491
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carotenoids in Human Skin

Abstract: The human skin, as the boundary organ between the human body and the environment, is under the constant influence of free radicals (FR), both from the outside in and from the inside out. Carotenoids are known to be powerful antioxidant substances playing an essential role in the reactions of neutralization of FR (mainly reactive oxygen species ROS). Carotenoid molecules present in the tissue are capable of neutralizing several attacks of FR, especially ROS, and are then destroyed. Human skin contains carotenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 102 publications
2
108
1
2
Order By: Relevance
“…Interest is growing in these xanthophylls, since several benefits to human health have also been attributed to them. There is an inverse relationship between the consumption of diets rich in carotenoids and the incidence of some kinds of cancer (lung, colon, and prostate) and the induction of skin deterioration by ultraviolet rays, cardiovascular diseases, cataracts, and macular degeneration (Beatty et al, 1999;Handelmen, 2001;Demmig-Adams and Adams, 2002;Johnson, 2002;Fraser and Bramley, 2004;Stahl and Sies, 2005;Darvin et al, 2011;Agarwal et al, 2012;Tanaka et al, 2012). Kuhnen et al (2011) have shown a fairly good content of these xanthophylls (lutein and zeaxanthin) in the kernel of MPA1-C0 compared to other local varieties maintained by farmers from the same region, besides its high-yielding potential and resistance to Exserohilum turcicum (Kist et al, 2010;Ogliari et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest is growing in these xanthophylls, since several benefits to human health have also been attributed to them. There is an inverse relationship between the consumption of diets rich in carotenoids and the incidence of some kinds of cancer (lung, colon, and prostate) and the induction of skin deterioration by ultraviolet rays, cardiovascular diseases, cataracts, and macular degeneration (Beatty et al, 1999;Handelmen, 2001;Demmig-Adams and Adams, 2002;Johnson, 2002;Fraser and Bramley, 2004;Stahl and Sies, 2005;Darvin et al, 2011;Agarwal et al, 2012;Tanaka et al, 2012). Kuhnen et al (2011) have shown a fairly good content of these xanthophylls (lutein and zeaxanthin) in the kernel of MPA1-C0 compared to other local varieties maintained by farmers from the same region, besides its high-yielding potential and resistance to Exserohilum turcicum (Kist et al, 2010;Ogliari et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…These grain colors (yellow or orange) reflect the concentration of xanthophylls, especially lutein and zeaxanthin (Pflffer and McClafferty, 2007;Rivera and Canela, 2012). Although they do not show any pro-vitamin A activity, the effects of these chemical constituents on human health have been widely reported in the literature, mostly concerning their preventive effects on age-related macular degeneration (Beatty et al, 1999;Handelmen, 2001;Demmig-Adams and Adams, 2002;Fraser and Bramley, 2004;Stahl and Sies, 2005;Kuhnen et al, 2009;Darvin et al, 2011;Agarwal et al, 2012;Rivera and Canela, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Resonance Raman spectroscopy was used in order to determine changes in the carotenoid concentration of the skin before and 24h after hair removal [23]. It has been shown in previous investigations that carotenoids can be measured as marker substance for the whole antioxidant status of the skin, since the antioxidant substances in the skin form protective chains that work against the destructive effects of free radicals [24,25].…”
Section: Resonance Raman Spectroscopymentioning
confidence: 99%
“…From these advantages, recent researchers have found to incorporate carotenoids into cosmetics such as skin lotions in order to enhance the ability of skin protection. However, the drawback of carotenoids is extremely sensitive to temperature, light and oxygen; thus, this compound is easily decomposed [5,6].…”
Section: Introductionmentioning
confidence: 99%